PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA NON FISIK TERHADAP LOYALITAS KARYAWAN MISKI AGHNIA CORPORATION - Jessica Alvina; Susanto, Andi Heru (Pusat Riset dan Inovasi Nasional, 2022)
Employee loyalty is a positive form or success of a company in managing its employess or human resources. When loyalty is high, the company’s goals will be easily achieved. This research seeks to understand the effect of workload and non-physical work environment on employee loyalty. To gain this understanding, this research uses a population of employees in Miski Aghnia Corporation. In this research, two types of variables were used, i.e. the independent variable which included workload and non-physical work environment, and the dependent variable, which is employee loyalty. To get valid results, this study uses a population of 95 employees. Regarding the sampling, this research used simple random sampling technique, with the framework for determining the sample using the Isaac and Michael table; meanwhile, to get an understanding of data collection, literature studies and questionnaires were used. After obtaining the required data, data analysis was carried out using descriptive statistics, validity and reliability instruments, classical assumption tests, simple linear regression, and hypothesis testing. In processing the obtained data, SPSS 25 for Windows research data processing tools are used. After an in-depth study, it was concluded that the workload had a positive and significant effect on employee loyalty. Besides, this research also concludes that the non-physical work environment has no positive and significant effect on employee loyalty.